Portfolio Optimization of Stocks in Different Industries by Single-Index Model and Markowitz Model - Chen Mingrui (SHS Web of Conferences)
In the financial sector, portfolio optimization is becoming more and more crucial. This article examines the portfolios of two industries, financial services and technology, in an effort to help prospective investors make decisions about their investments under a variety of constraints. The portfolio with the lowest volatility and the highest Sharpe ratio, and the constraint for the smallest value variance are the three practical restrictions that are paired with the Markowitz model and the Sharpe-single Index model approach to establish the ideal stock portfolios. The outcome demonstrates that, First, a risk-return portfolio can benefit from investing in the S&P index due to its strong correlation with listed companies; second, investing in the S&P index is preferred to hedge risk if short selling is prohibited; and third, it is advantageous to include the S&P index in the investment portfolio. This holds immense importance for the investigation of the most efficient distribution of monetary resources within the financial industry.